States of being+ (2022) experimental animation video - Synnos, Nicos (My University, 2021)
MeMeraki is hosting their second Annual Group Show from 8-15 of September 2022. With performances on the 8th and the 15th. It has been an even more challenging, tiring, exciting and inspirational year, with three back-to-back Residencies consisting of local and international artists. We are sustaining the dialogue between the local community and the art scene locally and internationally. Participating artists are Navin June Norling, Tamara Gonzales, Marios Pavlou, Gili Levy, Molly Lowe, Irene Zenonos, Iphigenia Papageorgiou, Iacovos Loizou, Maria Agisilaou, Katerina Savvides, Nicos Synnos, Christos Georgiou Titsiros, Maria Philippou, Ioanna Athanasiadou, Irenaeos Koullouras, Kalaqs.